Characterization of the Genome Feature and Toxic Capacity of a Bacillus wiedmannii Isolate From the Hydrothermal Field in Okinawa Trough - Zhao, Yan; Chen, Chen; Gu, Han-jie; Zhang, Jian; Sun, Li (Frontiers in Cellular and Infection Microbiology, 2019)
The Bacillus cereus group is frequently isolated from soil, plants, food, and other environments. In this study, we report the first isolation and characterization of a B. cereus group member, Bacillus wiedmannii SR52, from the hydrothermal field in the Iheya Ridge of Okinawa Trough. SR52 was isolated from the gills of shrimp Alvinocaris longirostris, an invertebrate species found abundantly in the ecosystems of the hydrothermal vents, and is most closely related to B. wiedmannii FSL W8-0169. SR52 is aerobic, motile, and able to form endospores. SR52 can grow in NaCl concentrations up to 9%. SR52 has a circular chromosome of 5,448,361 bp and a plasmid of 137,592 bp, encoding 5,709 and 189 genes, respectively. The chromosome contains 297 putative virulence genes, including those encoding enterotoxins and hemolysins. Fourteen rRNA operons, 107 tRNAs, and 5 sRNAs are present in the chromosome, and 7 tRNAs are present in the plasmid. SR52 possesses 13 genomic islands (GIs), all on the chromosome. Comparing to FSL W8-0169, SR52 exhibits several streaking features in its genome, notably an exceedingly large number of non-coding RNAs and GIs. In vivo studies showed that following intramuscular injection into fish, SR52 was able to disseminate in tissues and cause mortality; when inoculated into mice, SR52 induced acute mortality and disseminated transiently in tissues. In vitro studies showed that SR52 possessed hemolytic activity, and the extracellular product of SR52 exhibited a strong cytotoxic effect. These results provided the first insight into the cytotoxicity and genomic feature of B. wiedmannii from the deep-sea hydrothermal environment.